Q-switched and mode-locked erbium-doped fiber laser with Co-ZnO saturable absorber / Nusrat Khan Bintu - Nusrat Khan, Bintu (2017)
The aim of this thesis to show beat fiber lasers utilizing a cobalt-doped zinc oxide (Co-ZnO) based saturable absorber. At first, the generation of Q-switching pulces prepare has been effectively proposed and exhibited utilizing a cobalt-doped zinc oxide (Co-ZnO) nanorods as a SA. The proposed Q-switching Erbium-doped fiber laser (EDFL) works at 1559.0 nm utilizing the Co-ZnO SA film. Furthermore, A passive mode-locked EDFL was then shown in light of Co-ZnO nanorods SA using modified cavity. A long spool of SMF was consolidated into an EDFL to measure the depression to work in odd fiber scattering of - 4.571 ps2 administration. A steady self-began soliton pilses prepare was created at limit direct energy of 219 mW. The central wavelength and redundancy rate of the laser were 1559.5 nm and 1.007 MHz, respectively. The pulse width and most extreme energy vitality obtained aere 462.8 ns and 5.1 nJ, respectively at a direct energy of 248 mW. The Co-ZnO nanorods film was created by a straightforward preparing procedure, and it has a balance profundity of 6 % and immersing force of 60 MW/cm2.